Potensi Keunggulan Carica melalui Kurma Carica Khas Desa Atas Awan Berdasarkan Ethnoscience - Farah Afika Nur Jannah; Sri Jumini (Universitas Tadulako, 2022)
Cultural studies through ethnoscience support students' attitudes towards science. Therefore, its use in learning, especially for science students in physics learning materials related to the use of temperature during the production process still needs to be explored. This study aims to introduce the advantages of carica which can be explored through the production of carica dates which are endemic to the village of Atas Awan. This is because carica date products do not go through a boiling process which can damage the important ingredients in carica. This study used a qualitative descriptive research method with data collection techniques carried out through interviews, observation, and experiments. Based on the results of the study, it can be concluded that carica can be processed into various kinds of preparations that are in great demand and have many benefits, such as carica sweets, carica jam, carica chips, carica chocolate, carica batik, and carica dates. Processing carica into carica dates can be used as an ethnoscience medium to support students' attitudes towards science, especially science students in physics related to the use of temperature during the production process.